1992
DOI: 10.3341/kjo.1992.6.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Optic disc of the myopic eye: relationship between refractive errors and morphometric characteristics

Abstract: Because the optic disc in myopic eyes is different from a normal optic disc, there are many difficulties in examining the optic discs of myopic eyes. To study optic disc change due to myopia, we performed a morphometrical study of stereophotographs of 61 men, 109 eyes, who had no glaucoma history. The range of refractive error was from +0.75 diopter to -12.75 diopter, and all subjects had intraocular pressure below or equal to 21 mmHg. According to the increase in the myopic degree, the temporal slope of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 4 publications
2
30
2
Order By: Relevance
“…39 Although the OI is a gold standard for identifying ONH insertion obliqueness in myopic eyes, 23,40 its 2D characteristic does not take original optic disc shape into consideration. 40,41 We did not find evidence for an association between OI and SE (BF: 0.91) in our study and our result was in agreement with Takasaki et al 40 and Asai et al 23 who did not find a significant correlation between SE and OI as well. Although OI alone does not result in a satisfying model of SE, it has a strong modulatory effect in combination with other parameters, which is discussed in details further in this section.…”
Section: Discussionsupporting
confidence: 87%
“…39 Although the OI is a gold standard for identifying ONH insertion obliqueness in myopic eyes, 23,40 its 2D characteristic does not take original optic disc shape into consideration. 40,41 We did not find evidence for an association between OI and SE (BF: 0.91) in our study and our result was in agreement with Takasaki et al 40 and Asai et al 23 who did not find a significant correlation between SE and OI as well. Although OI alone does not result in a satisfying model of SE, it has a strong modulatory effect in combination with other parameters, which is discussed in details further in this section.…”
Section: Discussionsupporting
confidence: 87%
“…Optic disc area and area of the peripapillary region with chorioretinal atrophy were correlated with degree of myopia along with disc elongation, 64,[76][77][78][79][80] and the LC was shown to be thinner in highly myopic eyes than in nonhighly myopic eyes. 81 In highly myopic glaucomatous eyes, compared to nonhighly myopic glaucomatous eyes, optic disc area, elongation, cup length, and peripapillary atrophy were significantly larger, 32,33 LC was thinner, 81 and rim loss was greater.…”
Section: Peripapillary Bruch's Membrane Shapementioning
confidence: 94%
“…Curiously, in a different study no relationship was observed between ORA-measured corneal hysteresis and β -zone parapapillary atrophy 25 . Research also suggests that maximum deformation amplitude is associated to optic disc tilt, which, in turn, is closely related to myopia 26, 27 .…”
Section: Introductionmentioning
confidence: 99%